Mathematical modeling of mixing microjets of gas applied to the flaw detection problems - Skogsrod, T.; Sterten, Jo; Verlan, A.A. (Математичне та комп'ютерне моделювання. Серія: Технічні науки, 2015)
A mathematical model for the process of a gas jet outflow with account of diffusion in space filled with another gas is considered. A calculation algorithm is suggested for the concentration of the initial gas in the jet and the velocity of the mixed jet. The region of sharp change in the concentration of the initial gas is determined. The problem under consideration relates to the study of the processes of technical constructions tightness control and increasing sustainability of technological processes. Розглянуто математичну модель процесу відтоку газового струменя з урахуванням дифузії в просторі, що заповнений іншим газом. Запропоновано алгоритм розрахунку концентрації початкового газу в струмені і швидкості змішаного струменя. Визначено область різкої зміни концентрації початкового газу. Розглянута задача відноситься до проблем дослідження процесів контролю герметичності технічних конструкцій та підвищення сталості технологічного процесу.